Repair and Reconstruction of Bukhara Cultural Heritage Objects - Fattullayev Farrukh Fazliddin oglu (Researchparks Publishing, 2026)
This article scientifically analyzes the issues of repair and reconstruction of Bukhara cultural heritage objects. During the study, the importance of Bukhara architectural monuments as a unique example of Eastern architecture, the principles of preserving historical authenticity in their restoration, and the issues of restoring traditional architectural elements were covered. Also, the scientific and practical aspects of the restoration processes were analyzed using the example of the Samanid Mausoleum, the Poyi Kalon complex, the Ark fortress, the Mir Arab and Abdulazizkhan madrasas. The article also considers the state of preservation of cultural heritage objects in Uzbekistan, the level of tourist use, and existing problems. The results of the study show that scientific restoration, preservation of local traditions, and the development of sustainable tourism are important in preserving cultural heritage.